Pemutusan Hubungan Kerja (Phk) Sepihak terhadap Pekerja Hamil - Michellie Chandra Wijaya; Gunardi Lie (Syntax Literate, 2023)
Lack of focus on protecting the health, safety, and reproductive rights of female workers is a major contributor to the persistence of many labor issues. Unilateral termination of employment (PHK) carried out by the employer firm against pregnant workers is one of the elements producing issues in the sphere of labor. There is still widespread discrimination against pregnant workers in the workplace, which hinders the full realization of workers' rights such the protection of safety, health, and reproductive rights for women. Social security has been extended to female workers, for example, and the implementation is generally adequate, but there are certain aspects that are not yet appropriate, such as menstruation leave and maternity leave. The government's efforts to ensure the health, safety, and reproductive rights of pregnant workers are hampered by lax oversight from employers who often break the rules to their own gain